REVIEW OF SOME EUPHORBIACEAE PLANTS IN USADA TARU PRAMANA AND ITS PHARMACOLOGICAL ACTIVITIES - I Gede Bangkit Adi Sentosa; I Kadek Suardiana; A.A Gede Rai Yadnya Putra (Journal Pharmaceutical Science and Application, 2021)
Background: World Health Organization (WHO) states that up to 65% of the world's population uses traditional medicines. Indonesia is one of the countries where most people still use traditional medicine, especially in Bali. The traditional Balinese plant-based medical system that has existed for a long time and is still inherited today is Usada Taru Pramana. One of the many plants found in Usada Taru Pramana is the Euphorbiaceae. Objective: This work aims to review some of the Euphorbiaceae plants written in Usada Taru Pramana, which have a variety of potential pharmacological activities. Method: This article review using a primary and secondary data sources. Results: Some parts of the Euphorbiaceae plants in Usada Taru Pramana contain important phytochemical constituents such as phenols, alkaloids, flavonoids, saponins, tannins and essential oils. Some of the potential pharmacological activities that have been tested are anti-inflammatory, analgesic, and antibacterial. Conclusion: The Euphorbiaceae plants in Usada Taru Pramana have a variety of phytochemical constituents and correlates with its pharmacological activities. Further research needs to be conducted to explore other Euphorbiaceae plants species in Usada Taru Pramana to find compounds and other pharmacological activities to deal with various diseases in the community. Keywords: Usada Taru Pramana, Euphorbiaceae, Phytochemical Constituents, Pharmacological Activities.